Using forensic handwriting principles for rapid signature screening - Craythorne, Brian (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Examination of a signature is a lengthy process conducted under laboratory conditions, requiring precision and caution. When a rapid screening of signatures is required, the basic principles of forensic signature comparison can be adapted. Learning points from signature screening examinations are outlined to aid handwriting experts in carrying out similar procedures.
Keywords: badanie podpisu; badanie przesiewowe; najlepsze praktyki; komparatystyka